Knowledge and Attitudes toward Sexual Abuse are Positively Correlated with Parents' Self-Efficacy in Preventing Child Sexual Abuse - Selviana, Selviana; Suwarni, Linda (Journal of Health and Nutrition Research, 2025)
Child sexual abuse (CSA) is a public health problem that requires serious attention from all parties, including parents, as the frontline in protecting children. This study aims to analyze the correlation between parents' knowledge, attitude, and self-efficacy in preventing child sexual abuse in Sambas Regency. The study used a quantitative design with a cross-sectional design on parents (n=30), selected through a purposive sampling technique. Data were analyzed using Pearson’s correlation test with a significance level of α=0.05. The results showed that 56.7% of respondents had good knowledge and 53.3% had a positive attitude, but 53.3% still had low self-efficacy in preventing child sexual abuse. There was a significant positive correlation between knowledge and attitude (r=0.518, p=0.003), knowledge and self-efficacy (r=0.587, p=0.001), and attitude and self-efficacy (r=0.378, p=0.039). These findings indicate that higher parental knowledge correlates with more positive attitudes and greater self-efficacy in preventing child sexual abuse. This study suggests developing a comprehensive intervention program that simultaneously focuses on strengthening these three aspects, with a culturally sensitive approach to overcome communication barriers about sexuality.